An econometric model on bilateral trade in education using an augmented gravity model - Christina Tay (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: Trade in education has become one of the most important trades for many economies. Yet, studies of education as a trade are scant owing to the conventional view of it being non-tradable. The purpose of this paper is to econometrically investigate trade in education using a nexus of international trade theories and the gravity model, one of the most widely used models in international trade in goods that has been scantly investigated on in studies on trade in education. Design/methodology/approach: A panel data analysis is broken down for 21 exporting countries and 50 importing countries, covering 1050 observations using new UNESCO database. A number of determinants of international trade including wealth of exporter & importer, domestic capacity of exporter & importer, transport costs, common religion, common language and trade restrictiveness of the importer are empirically tested on bilateral trade flows in education. An econometric model is formulated to test determinants of trade in education using an augmented gravity model. Findings: The augmented gravity model used in this study explains with high significance the determinants of trade in education including wealth of exporter & importer, domestic capacity of exporter & importer, transport costs, common religion, common language and trade restrictiveness of the importer. Research limitations/implications: Taking a macroscopic view of education as a trade may give us a myopic view of the elements important to determine what students or parents of students as well as institutions are concerned with. Nevertheless, the nexus of international trade theories and the gravity model used in this study that are largely and traditionally used on trade in goods and services, but scantly used in trade in education have been found to be highly significant and relevant in trade in education. Future studies on macro-level of analysis involving trade in education could include other determinants of trade in education or trade in goods/services to test for their relevance and significance in this area of study. Practical implications: This paper aims to contribute to existing literature on trade in services and trade in education by borrowing some of the same assumptions on market structures usually made for services and international trade to show that the international trade theories can help explain the pattern of trade in education. The econometric model formulated enables governments to design policies that could facilitate, direct and promote the development and growth of education as a trade. It could also assist institutions to adjust and choose more efficient methods of structuring their policies and formulating their marketing strategies, targeted towards different country segments. Social implications: With the share of education services in world trade increasing, it becomes even more important to be able to accurately model trade in education services. Thus, my introduction of the augmented gravity model on trade in education provides new and interesting avenues for further macro research of trade in education on an international platform. Originality/value: I borrow the same assumptions on market structures usually made for services to show that international trade theories can help explain the pattern of trade in education. This paper proposes an effective econometric model using the gravity equation to help governments as well as institutions evaluate the importance of the various determinants of trade in education.
Keywords: 650; trade in services; international trade; trade in education; gravity model; trade restrictiveness; Generally Accepted Trade in Services(GATS); consumption abroad